The Vonnegut Effect - Klinkowitz, Jerome (Book collections on Project MUSE., 2010)
"A pioneer in Vonnegut studies and publishing in the field since 1969, Klinkowitz offers The Vonnegut Effect as a thorough treatment of the author's fiction - a canon covering more than a half century and comprising twenty books. Considering both Vonnegut's methods and the cultural needs they have served, Klinkowitz explains how those works came to be written and concludes with an assessment of the author's place in the tradition of American fiction"--Page 4 of cover